Microsatellite variation in Nordic semi-domestic reindeer ... - Røed, Knut; Kvie, Kjersti; Bårdsen, Bård-Jørgen; Laaksonen, Sauli; Lohi, Hannes; Kumpula, Juoko; Aronsson, Kjell-Åke; Åhman, Birgitta; Våge, Jørn; Holand, Øystein (Dryad, 2021)
We have analyzed DNA microsatellites and the mitochondrial control region in reindeer from 31 different husbandry areas in Norway, Sweden and Finland in order to better understand the processes that underlie the genetic variability of the Nordic domestic herds. The distinct differentiation found in the nuclear markers but less so in the mitochondrial marker, gives evidence of an origin from a common ancestral population which later evolved into the two main gene pools characterizing the nuclear genomes of domestic reindeer in Finland and most of Sweden and Norway. Analyses of temporal trends in effective population size gives evidence of a rapid increase in number of reindeer before the population growth associated with the pastoral transition. This implies that the ancestry of contemporary domestic reindeer lay among a rapid growing wild population possibly located in the boreal areas of eastern Fennoscandia or European Russia. The evolution of reindeer husbandry in Finland, perhaps with input from European ... : DNA was extracted from blood and tissue samples using DNeasy Blood and Tissue Kits (Qiagen). 904 reindeer samples from 31 reindeer herding districts in Norway, Sweden and Finland were analyzed for 18 microsatellite loci amplified by PCR and scored as product sizes. ...